A Study of LES Stress and Flux Models Applied to a Buoyant Jet - Worthy, Jude; Rubini, Philip A. (Taylor and Francis, 2005)
Large eddy simulation (LES) stress and scalar flux subgrid scale models are evaluated in the context of buoyant jets. Eddy viscosity, eddy diffusivity (including formulations of the generalized gradient diffusion hypothesis), “structure” (Bardina and Leonard), mixed, and dynamic models are scrutinized. The performance of the models is examined in terms of the main flow variables and also with respect to the “internal” behavior of the models in terms of the relative contributions to the turbulent kinetic energy budget.